Dagblad van Noord-Brabant : . Dagblad van Noordbrabant en Zeeland
Ook o.d.t.: Dagblad van Noordbrabant. - Vanaf 74(1934):no.15052 o.d.t.: Dagblad van Noordbrabant en Zeeland. - 30(1934):no.123 o.d.t.: Dagblad van Zeeland...